1881 Ind. Acts 191, ch. 37, § 81 - (:unkn) unknown (General Publisher, 1881)
Prohibited drawing or threatening to use any pistol, dirk, knife, slung-shot, or any other deadly or dangerous weapon. Violators guilty of a misdemeanor, fined not less than one but no more than five hundred dollars. Violators may also be subject to imprisonment not exceeding six months.
--
Keywords: BRANDISHING